2015
DOI: 10.1590/s1517-838246420140410
|View full text |Cite
|
Sign up to set email alerts
|

Molecular variations in Vibrio alginolyticus and V. harveyi in shrimp-farming systems upon stress

Abstract: A study was performed to investigate the genomic variations in the shrimp farm isolates of Vibrio alginolyticus and V. harveyi when the isolates were subjected to environmental stress. Samples of shrimps, water and sediment were collected from Southern Indian coastal shrimp farms. Vibrio isolates were biochemically identified and confirmed using 16S rDNA and gyrB gene specific PCR. The bacterial strains were genotyped by PCR fingerprinting using GTG(5) and IS (Insertion Sequence) primers. Seven strains each of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Several lines of evidences indicate that V. alginolyticus has developed several strategies to cope with antibiotics, including gene mutation of target proteins, transfer of antibiotic resistance plasmids, decrease in permeability, and activation of an efflux system such as TolC (Hayashi et al, 2002;Xiong et al, 2010;Lajnef et al, 2012;Li et al, 2012;Giedraitiene et al, 2011;Miller et al, 2014). V. alginolyticus lives in the optimum salt concentration ranging from 2.5% to 4.5% NaCl (average NaCl concentrations in the sea are~3.5%) but can survive in a wide range of NaCl concentrations from 0.5% to 12% NaCl (Santhyia et al, 2015;Liu et al, 2004), where the range of 0.5% to 4% NaCl is the conventional environmental condition under which Vibrio species survive. Thus, it is interesting to explore whether NaCl concentration affects the antibiotic resistance in Vibrio species.…”
Section: Discussionmentioning
confidence: 99%
“…Several lines of evidences indicate that V. alginolyticus has developed several strategies to cope with antibiotics, including gene mutation of target proteins, transfer of antibiotic resistance plasmids, decrease in permeability, and activation of an efflux system such as TolC (Hayashi et al, 2002;Xiong et al, 2010;Lajnef et al, 2012;Li et al, 2012;Giedraitiene et al, 2011;Miller et al, 2014). V. alginolyticus lives in the optimum salt concentration ranging from 2.5% to 4.5% NaCl (average NaCl concentrations in the sea are~3.5%) but can survive in a wide range of NaCl concentrations from 0.5% to 12% NaCl (Santhyia et al, 2015;Liu et al, 2004), where the range of 0.5% to 4% NaCl is the conventional environmental condition under which Vibrio species survive. Thus, it is interesting to explore whether NaCl concentration affects the antibiotic resistance in Vibrio species.…”
Section: Discussionmentioning
confidence: 99%
“…SEM images showed that it was short‐rod‐shaped with a curved body and no budding spores, pods and flagella. Vibrio , as an opportunistic pathogen, widely exists in aquaculture water environment, which can lead to disease and even the death of shrimp in numerous reports (Nguyen et al, 2021; Santhyia et al, 2015; Zhou et al, 2012). At present, antibiotics are still the main drugs for the control and treatment of Vibrio diseases (Brumfield et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have shown that Photobacterium can cause various diseases in fish and shrimp (Vaseeharan et al, 2007; Kanchanopas-Barnette et al, 2009; Zhang et al, 2011; Singaravel et al, 2020; Wang et al, 2020), causing huge losses in aquaculture. Vibrio harveyi, Vibrio alginolyticus and V. parahaemolyticus are three species of Vibrio , which are considered to be the main opportunistic pathogens in shrimp disease outbreaks (Zhou et al, 2012; Santhyia et al, 2015; Nguyen et al,2021). These results suggested that intestinal pathogenic bacteria were increased after DIV1 infection, which may probably because the DIV1 infection disrupted the mechanical barrier of the intestine and impaired the ability of intestine to select microorganisms.…”
Section: Discussionmentioning
confidence: 99%